Genetic architecture of primary biliary cholangitis: strong evidence for HLA and non-HLA risk loci - Zhang, Min; Lyu, Liang; Ge, Liang; Wang, Yizhou; Gu, Dongqing (Frontiers in Immunology, 2025)
BackgroundDespite extensive genetic studies investigating primary biliary cholangitis (PBC), the mechanistic basis of risk-associated variants remains poorly understood. To address this gap, we performed a systematic evaluation of cumulative evidence linking genetic variants to PBC susceptibility.MethodsA comprehensive search was conducted to identify published studies on the association between genetic variants and PBC risk. Specifically, separate analyses were conducted for genome-wide association studies (GWASs) and candidate-gene association studies to address potential heterogeneity arising from differences in study design. Meta-analyses were performed to calculate pooled odds ratio (OR) and 95% confidence interval (CI) for the candidate-gene association studies. Significant associations were further graded using Venice criteria and false-positive report probability (FPRP) tests. Functional annotation, pathway enrichment, and phenome-wide analyses were performed to elucidate biological relevance.ResultsOverall, we included 105 articles involving 71,031 cases and 140,499 controls. Meta-analyses were conducted for 70 variants across 33 genes. Among these, 44 variants were identified as significantly associated with PBC risk, comprising 30 HLA variants and 14 non-HLA variants. Separately, published GWAS have reported 115 significant variants. Nine variants (DQA1*0401, DQB1*0301, DQB1*0402, DQB1*0602, DRB1*08, DRB1*0803, DRB1*11, DRB1*1101, and rs7574865) were identified by both approaches. Additionally, meta-analyses of candidate-gene association studies provided strong evidence supporting the association of eight further variants (A*3303, B*4403, DPB1*0201, DQB1*0401, rs231725, rs231775, rs1544410, and rs9303277) with PBC at the genome-wide significance level (P < 5.0 × 10-8). Pathway analysis revealed significant enrichment of the mapped genes in immune cell regulation and immune response-regulating signaling pathways. Phenome-wide analyses further indicated that the missense variant rs231775 was significantly associated with thyroid problems and melanoma (P< 6.43×10-5).ConclusionThis study provides the most comprehensive synopsis to date of PBC’s genetic architecture, highlighting robust HLA and non-HLA risk loci.Systematic review registrationhttps:///www.crd.york.ac.uk/PROSPERO/view/CRD42021282146, identifier CRD42021282146.